2018
DOI: 10.1096/fj.201800346r
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 Q192R genotype and activity affect homocysteine thiolactone levels in humans

Abstract: Genetic or nutritional deficiencies in 1 carbon and homocysteine (Hcy) metabolism elevate Hcy-thiolactone levels and are associated with cardiovascular and neurologic diseases. Hcy-thiolactone causes protein damage, cellular toxicity, and proatherogenic changes in gene expression in human cells and tissues. A polymorphic cardio-protective enzyme, paraoxonase 1 (PON1), hydrolyzes Hcy-thiolactone in vitro. However, whether Hcy-thiolactone hydrolysis is a physiologic function of the PON1 protein and whether polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 48 publications
(77 reference statements)
2
21
0
Order By: Relevance
“…1) include methionyl-tRNA synthetase (MARS), responsible for the synthesis of Hcy-thiolactone [9,10] and HTases such as PON1, BLMH and BPHL [45][46][47][48], which are responsible for Hcy-thiolactone hydrolysis. Indeed, recent studies found that PON1 Q192R genotype and activity affect Hcy-thiolactone levels in humans [49] and that among CAD patients undergoing percutaneous coronary intervention those with low serum HTase activity show significantly higher all-cause mortality than patients with high HTase activity [50].…”
Section: Discussionmentioning
confidence: 99%
“…1) include methionyl-tRNA synthetase (MARS), responsible for the synthesis of Hcy-thiolactone [9,10] and HTases such as PON1, BLMH and BPHL [45][46][47][48], which are responsible for Hcy-thiolactone hydrolysis. Indeed, recent studies found that PON1 Q192R genotype and activity affect Hcy-thiolactone levels in humans [49] and that among CAD patients undergoing percutaneous coronary intervention those with low serum HTase activity show significantly higher all-cause mortality than patients with high HTase activity [50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the same study, a frequent polymorphism in PON2 , encoding a cellular antioxidant enzyme of the paraoxonase family that protects cells against oxidative stress, was associated with accumulation of HTL [149]. Similarly, a frequent polymorphism in PON1 , which encodes a cardio-protective enzyme known to hydrolyze HTL in vitro, was shown to elicit elevation of urinary HTL levels [150]. Homocysteine thiolactonase activity was also negatively associated with the thickness of the carotid intima media in patients with type 2 diabetes mellitus [151].…”
Section: Mechanisms Induced By Hhcy Associated With Endothelial Dymentioning
confidence: 99%
“…This increasingly prominent protein modification, called N-homocysteinylation, seems to exert cytotoxic, pro-inflammatory, prothrombotic, and pro-atherogenic properties, contributing to the cardiovascular and neurologic disorders of hyperhomocysteinemia (HHcy) [17,18]. Perła-Kaján et al [19] demonstrated that Hcy-thiolactone-hydrolyzing enzymes, known as the paraoxonase (PON) multigene family, associated in the bloodstream with high-density lipoproteinis (PON1/HDL) detoxify homocysteine thiolactone. Therefore, genetic variation in PON1 could compromise this activity in humans.…”
Section: Introductionmentioning
confidence: 99%